O Instituto de Matemática e Física da Universidade da Bahia: atividades matemáticas (1960-1968) The Instituto de Matemática e Física at the Universidade da Bahia: mathematical activities (1960-1968) - André Luís Mattedi Dias (História, Ciências, Saúde: Manguinhos)
Analisa o processo de implantação de Instituto de Matemática e Física da Universidade da Bahia entre 1960 e 1968. Enfatiza os diversos interesses, representações, articulações, convencimentos e conflitos que envolveram os participantes do processo. Por um lado, o projeto inicial de Martha Dantas, Arlete Cerqueira Lima e Ramiro Porto Alegre, patrocinado pelo reitor Edgard Santos e encampado por Rubens Lintz, Omar Catunda e Leopoldo Nachbin, foi contestado pelos catedráticos da Escola Politécnica, representados por Bautista Vidal; por outro, os estudantes da Escola Politécnica não seguiram as atividades de iniciação científica desenvolvidas no Instituto, que só despertaram o interesse de estudantes oriundas da Faculdade de Filosofia. The article analyzes the process of setting up the Institute of Mathematics and Physics at the University of Bahia during 1960-1968. The focus is on the various interests, representations, articulations, convictions, and conflicts in which a good share of the participants were involved. On the one hand, Martha Dantas, Arlete Cerqueira Lima, and Ramiro Porto Alegre's original project - sponsored by Rector Edgard Santos and embraced by Rubens Lintz, Omar Catunda, and Leopoldo Nachbin - was challenged by professors holding chairs in engineering at the Polytechnical School and the School of Philosophy, represented by Bautista Vidal. On the other, students at the Polytechnical School did not engage in the scientific research activities conducted at the Institute, which captured the interest only of students from the School of Philosophy.